Organic–Inorganic Hybrid Interfaces for Spin Injection into Carbon Nanotubes and Graphene. Issue 6 (30th March 2022) - Martin, Pascal; Dlubak, Bruno; Seneor, Pierre; Mattana, Richard; Martin, Marie‐Blandine; Lafarge, Philippe; Mallet, François; Della Rocca, Maria Luisa; Dubois, Simon M.‐M.; Charlier, Jean‐Christophe; Barraud, Clément
Abstract: Spintronics is a quantum technology which aims at adding the spin quantum degree of freedom to conventional CMOS electronics. Since the discovery of the giant magneto‐resistance in 1988, considered as the birth of this field, spintronics continues flooding the market with plethora of devices used in everyday life applications such as hard drive read heads or magnetic random‐access memories, and so on. From a fundamental research perspective, the field is still blooming bringing post‐CMOS perspectives technologically closer to the reality with, for instance, prototypes of all‐spin‐logic circuits and neuromorphic chips. To sustain this intense research activity, a quest for new platform materials is also taking place not only to enhance existing performances but also to generate novel functionalities. In this vein, carbon nanostructures such as molecules, graphene, and carbon nanotubes are among the most sought‐after materials. In this review, spin transport experiments in carbon nanotubes and graphene are first detailed and then, the necessity to consider new hybrid interfaces are highlighted for a better control of the spin injection at the quantum device level. Abstract : In this review, the recent progresses, understandings, and results obtained with the implementation of hybrid organic molecules/ferromagnetic metal interfaces in spintronics devices based on graphene and carbon nanotubes are highlighted and discussed. Focus is given on the physical and chemical compatibility between the materials to reach exceptional figures of merit in the next generation of spintronics devices.